Opportunities and threats of digital transformation management education - T. Yu. Krotenko (Цифровая социология)
The changes taking place in the world presuppose the inevitable entry of business, science, education into the digital space. For such a serious step, Russian organisations in any ﬁeld of activity need a comprehensive readiness of the entire system, supported not only by the enthusiasm of employees and the ability of managers to experiment. Without thoughtful high-quality preparation of all system elements and connections, digital transformation can turn out to be an untimely costly measure that hinders the development of organisations. The article analyses the barriers to the economic digitalisation and management education that affect the digital transition success. Education is viewed as a leading factor in socio-economic development, therefore, the demand for digitalisation is addressed primarily to education. The article raises the problem of the lack of a convincing scientiﬁc psychological and pedagogical concept of digital learning, which could be used by subjects of education as a basic one. The results of a students’ survey of management specialties of the university showed: the professional competencies of modern managers necessary for activities in the era of the digital revolution have to be expanded, the question arises of the reasonable disciplines inclusion that correspond to real needs in the educational programs of the management university.